2017
DOI: 10.1177/1350650117724639
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective optimization of thermohydrodynamic journal bearing using MOPSO algorithm

Abstract: This article focuses on the use of multiobjective particle swarm optimization algorithm in combination with the thermohydrodynamic governing equations of fluid film (i.e. momentum and energy equations) in developing an efficient design method to optimize hydrodynamic partial pad journal bearings, for the first time. The governing equations are solved by using the central difference technique with a successive over relaxation scheme. In the simulation, the lubricant viscosity is changed with the temperature var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The programming code is similar to the one used and validated in the study by. Akbarzadeh 23 and Akbarzadeh et al 12 Besides, for optimizing procedure of the solver, another programming code (written in FORTRAN) has been developed of which algorithm is reported by a flowchart in Figure 2.…”
Section: Solving Equation (16) By a Backward Differencementioning
confidence: 99%
See 2 more Smart Citations
“…The programming code is similar to the one used and validated in the study by. Akbarzadeh 23 and Akbarzadeh et al 12 Besides, for optimizing procedure of the solver, another programming code (written in FORTRAN) has been developed of which algorithm is reported by a flowchart in Figure 2.…”
Section: Solving Equation (16) By a Backward Differencementioning
confidence: 99%
“…Results of the optimization process. 4,6,12,15 Design Figure 6. Results of the optimization process.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Raimondi and Boyd [5][6][7] with helping Reynolds equation performed some numerical studies in the field of journal bearings. After that, many researches developed the lubrication theory and implemented it to analyze the performance of various types of bearings using Newtonian lubricant model such as Raimondi, 8 Dowson, 9 Malik, 10 Elsharkawy, 11 Shah and Bhat, 12 Shenoy and Pai, 13 Gustavo et al, 14 Sfyris and Chasalevris, 15,16 Rao et al, 17 Ram and Sharma, 18,19 Jang and Khonsari, 20 Akbarzadeh, 21 Gong et al, 22 Akbarzadeh et al, 23 Novotny´et al, 24 Li et al, 25 Novotny´et al, 26 Yu et al, 27 to name a few. In fact, these studies played a key role in the development of mathematical modeling for hydrodynamic journal/ thrust/sliding bearings and the increase of the accuracy of computational methods and their adaptation to experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that the pivot position, preload factor, pad number, and speed of shaft is greatly influences the performance of journal bearing. Akbarzadeh et al 12 used the multi-objective particle swarm optimization algorithm for solving the partial pad hydrodynamic journal bearings problem. The optimization results were depicted in the form of Pareto curves/tabular form and the effect on pad temperature, minimum oil film thickness and frictional power loss studied.…”
Section: Introductionmentioning
confidence: 99%